115k views
2 votes
Please help me out I don’t get it and went over it and keep on making a mistake

Please help me out I don’t get it and went over it and keep on making a mistake-example-1

1 Answer

4 votes

We have the height of the first two bounces. The first one is 6 feet, while the second is 4 feet. We need to find the ratio between the first and second bounces:


\text{ratio}=(4)/(6)=(2)/(3)

Therefore the equation for the bounces is:


\begin{gathered} h(n)=6\cdot((2)/(3))^(n-1) \\ h(n)=6\cdot((2)/(3))^n\cdot((2)/(3))^(-1) \\ h(n)=6\cdot((2)/(3))^n((3)/(2)) \\ h(n)=9\cdot((2)/(3))^n \end{gathered}

User Shane Tomlinson
by
5.1k points